Effect of Distant Learning and Face-To-Face Learning on Student Performance and Perception in the Psychiatric Undergraduate Educational Module at King Abdulaziz University - Dr. Faten Al Zaben,; Hind Fallatah , (Journal of King Abdulaziz University: Medical Sciences, 2024)
Background: The outbreak of the COVID-19 global health crisis raised significant challenges in medical education due to the disruption of academic institutions' educational systems. The emergency lockdown instigated the closure of conventional educational activities and encouraged electronic portal learning as an alternative strategy. Tremendous efforts have been made by the dedicated and determined faculty of medicine at King Abdulaziz University to include distance learning as part of the educational process and face-to-face learning for the past few years. Considering the pandemic scenario, many policies were postulated at King Abdulaziz University to generate flexible, convenient, standardized, and modern modes of education. Therefore, this study examined students' perception of distance learning and how teaching methods and curriculum design affect students’ performance. Method: This cross-sectional survey study enrolled a total of 126 students who participated in this study from January 2020 to April 2020. Results: The results showed higher mean total satisfaction in the E-learning group compared to face-to-face learning with no statistically significant difference (p > 0.05). Comparison between E-learning and face-to-face learning regarding course objectives showed a highly statistically significant difference (p < 0.05). The teacher feedback provided during the course also showed statistically significantly improved results in the E-learning group (p < 0.05). Conclusion: It is recommended that both types of learning be blended as a "blended learning or hybrid learning” model, which will have advantages for both types of learning systems and can solve problems that may arise by using only one kind of learning. This field requires more research, especially longitudinal studies, to determine long-term effectiveness